Explaining and Designing a Model for Human Capability Development in the Banking System (Case Study: Bank Melli Branches Abroad) - Sardari Baf, Iraj; Seyed Javadin, Seyed Reza; Amiri, Mojtaba; Hasangholipoor, Tahmoors (Assessment and Practice in Educational Sciences, 2024)
The purpose of this study is to explain and design a model for human capability development in the banking system, focusing on the case study of Bank Melli branches abroad. The study is exploratory and interpretive in nature and employs a mixed-methods approach. The term “mixed” refers to the combination of both quantitative and qualitative research methods. Due to the nature of mixed-methods research, the statistical population was divided into two phases: participants in the qualitative phase and the statistical population and sample drawn from it in the quantitative phase. In the first phase, the sampling method was based on the snowball technique. Consequently, the sample size was determined by reaching theoretical saturation. In the second phase, the population consisted of experts, managers, and employees of Bank Melli branches abroad. The sample size in this phase was calculated using Cochran’s formula and selected through convenience sampling. To collect data, both library research and survey methods were employed. The current study was conducted in two sections—qualitative and quantitative. In the qualitative section, thematic analysis based on the King and Horrocks approach was used. In the quantitative section, to analyze the data and conduct inferential analysis, factor analysis and structural equation modeling (SEM) were utilized, with the aid of SmartPLS software. Based on the analyses, the study concluded that several factors play a significant and meaningful role in the overall model of human capability development in the banking system. These factors fall into the following general categories: general communication skills, general executive skills, professional knowledge, individual professional skills, and organizational capability.